Temperaturne razmere v dotikih z jeklenimi in kompozitnimi zavornimi diski C/C-SiC - Kermc, Mihael (Strojniški vestnik, 2004)
Automotive braking systems normally employ conventional or ventilated brake discs and pads. In these systems the brake discs are made of steel or grey cast iron, which are paired with composite "organic" brake pads. Car manufacturers, however, are designing larger and heavier vehicles, with more powerful engines, which results in higher driving speeds and greater demands being placed on the frictional power of the brake systems. Improving the performance of a braking system requires either a larger conventional brake, which is not the best solution, or the use of new, improved brake-disc and padmaterials. One such promising material for brake-disc applications is a C/C-SiC composite. However, despite its low wear rate and high frictional power, its use is still very limited because of the lack of an appropriate padmaterial that will perform well in combination with these discs under the conditions that are experienced with mass-production vehicles. One of the mainreasons for this is the supposed high temperatures generated in these contacts. However, since this research is in its early stages and because of the particular materials and their combinations, relevant data on this topic cannot be obtained from the literature. Our first step in the development of apad material for our own design of C/C-SiC composite discs was to determine the contact temperature and make a comparison with conventional steel discs under the same conditions. The evolution of the contact temperature was studied using two different testing machines and methods, where we simulated the dynamic braking conditions that are similar to those observed in real applications and under steady-state conditions. The differences could be explained by the thermal properties of the materials. All the experiments usedthe same pads, which were made from a metal-matrix composite to our own design.
Keywords: diski zavorni; litina jeklena; C/C-SiC kompoziti; razmere temperaturne; zavorni diski; materiali; kompoziti; temperatura